Heterogeneous, Longitudinally-Stable Molecular Signatures in Response to Interferon-β - Sandhya Rani, M. R. (2009)
Interferons (IFNs) are widely used in therapy for viral, neoplastic and inflammatory disorders, but clinical response varies among patients. The biological basis for variable clinical response is not known. We determined the primary molecular response to IFN-beta (IFN-β) injections in 35 treatment-naïve multiple sclerosis (MS) patients using a customized cDNA macroarray with 186 interferon-stimulated genes (ISGs). Our results revealed striking inter-individual heterogeneity, both in the magnitude as well as the nature of the primary molecular response to IFN-β injections. Despite marked between-subject variability in the molecular response, responses within individual subjects were stable over a six-month interval. Our data suggest that clinical response to IFN-β therapy for MS differs among patients because of qualitative rather than quantitative variability in the primary molecular response to the drug.